2014
DOI: 10.15261/serdj.21.201
|View full text |Cite
|
Sign up to set email alerts
|

Water / Methyl isobutyl ketone (MIBK) Biphasic System in Slug Flow under High Temperature and Pressure Conditions

Abstract: The clarification of the partition property of substrates in a water / organic biphasic system is useful in the development of a reaction / separation process for value-added materials, especially under high temperature and pressure conditions. In this study, the water / methyl isobuthyl ketone (MIBK) biphasic system was investigated under various temperatures (25 -190 o C) at 10 MPa. The partitioning behavior of substrates such as furfural derivatives, amino acids, and saccharides, depended on the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…We assumed the slug flow with the wall film in the tube, as shown in Figure b. This is because the slug flow was observed under low temperature conditions, as previously reported . Assuming a linear driving force approximation as previous reported, the mass transfer rate of HMF from the aqueous to the organic phase can be described.…”
Section: Theoretical Sectionmentioning
confidence: 93%
See 3 more Smart Citations
“…We assumed the slug flow with the wall film in the tube, as shown in Figure b. This is because the slug flow was observed under low temperature conditions, as previously reported . Assuming a linear driving force approximation as previous reported, the mass transfer rate of HMF from the aqueous to the organic phase can be described.…”
Section: Theoretical Sectionmentioning
confidence: 93%
“…In our previous study, it has been reported that a liquid–liquid slug flow of water/methyl isobuthyl ketone (MIBK) biphasic system in T‐junction microcapillary was advantageous for the reaction of fructose to HMF in comparison of reactor type between the batch and flow systems . Likewise, the above slug flow had the enhanced mass transfer of 17 kinds of compounds from water to MIBK phase . We have developed the reaction kinetic model taking into consideration of the mass transfer for HMF between water and organic phases, and there is lack of investigations relating to the mass transfer of HMF and the fluid dynamics in slug flow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has low hazardousness and already gave promising results in previous publications [3,[10][11][12][13][14][15][16][17]. Other applied solvents are ethyl acetate and 2-heptanone which have similar abilities to dissolve 5-HMF.…”
Section: Introductionmentioning
confidence: 99%